2011
DOI: 10.1007/s13594-011-0026-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of milk electroreduction: impact of low anode/cathode voltage difference application on its redox potential modulation during treatment and storage

Abstract: To cite this version:Bazinet, Schreyer, Lessard. Optimization of milk electroreduction: impact of low anode/cathode voltage difference application on its redox potential modulation during treatment and storage. Dairy Science Abstract Milk degradation during processing and storage is mainly due to oxidation-reduction reactions. Electroreduction was proposed recently to modulate the redox potential of food such as milk. However, only one study was carried-out on milk with a hydrodynamic electroreduction cell, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, none of the working groups before differentiated the effect of the outer phase and the feed solution, but Bolduc et al (2006) and Bazinet et al (2011) also reported about the effect of the oxido-reduction potential of skimmed milk between voltages of 2-10 and 1.5-3.5 V. Bolduc et al (2006), for example, described the optimal fractionation to be at a voltage of 4 V, while increasing voltage results in the formation of foam, and thus, water hydrolysis in milk takes place. The experiments performed by Bazinet et al (2011), who worked in a narrower brand, showed that between 1.5 and 2.5 V, the effect is only low, while over a level of 3 V, there are great differences. Compared to that, an electrical potential between 8 and 16 V is sufficient enough for the production of electrolyzed water in the food industry, which was reported by Huang et al (2008).…”
Section: Electrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, none of the working groups before differentiated the effect of the outer phase and the feed solution, but Bolduc et al (2006) and Bazinet et al (2011) also reported about the effect of the oxido-reduction potential of skimmed milk between voltages of 2-10 and 1.5-3.5 V. Bolduc et al (2006), for example, described the optimal fractionation to be at a voltage of 4 V, while increasing voltage results in the formation of foam, and thus, water hydrolysis in milk takes place. The experiments performed by Bazinet et al (2011), who worked in a narrower brand, showed that between 1.5 and 2.5 V, the effect is only low, while over a level of 3 V, there are great differences. Compared to that, an electrical potential between 8 and 16 V is sufficient enough for the production of electrolyzed water in the food industry, which was reported by Huang et al (2008).…”
Section: Electrolysismentioning
confidence: 99%
“…Major advantages superimposing an electrical field during cross-flow ultrafiltration are a selective fractionation based on the physicochemical properties of molecules (size, charge, and adsorption characteristics). Electrophoresis principle applied in electrodialysis and pressure-driven filtration cell has been used for nutraceutical applications, such as the isolation of bioactive peptides and amino acids (Bargeman et al 2002;Daufin et al 1995;Poulin et al 2006), for the isolation of lactoferrin (Brisson et al 2007;Ndiaye et al 2010) and bovine serum albumin (Robinson et al 1993) in food processing, or the filtration of oily wastewater (Huotari et al 1999), as well as for agricultural purposes, such as the separation of protein or microbial cell suspensions (Bazinet et al 2011;Chuang et al 2008). In addition, a phenomenon called electrolysis occurs when an aqueous solution is subjected to an external field (Shaposhnik and Kesore 1997).…”
Section: Introductionmentioning
confidence: 99%